2000
DOI: 10.1034/j.1600-0722.2000.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorpromazine on alveolar bone loss in experimental periodontal disease in rats

Abstract: Chlorpromazine (CPZ), a phenothiazine derivative, possesses anti-inflammatory properties, inhibition of tumor neurosis factor-alpha (TNF-alpha) synthesis and bone resorption. TNF-alpha promotes inflammatory changes and bone resorption in periodontitis. We have studied the effect of CPZ in experimental periodontitis. Wistar rats were subjected to a ligature placement around the cervix of the right second upper molars. Alveolar bone loss was evaluated by the sum of the distances between the cusp tip and the alve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
107
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 11 publications
12
107
0
8
Order By: Relevance
“…In addition to the heart tissues, maxillary samples were taken by decapitating the rats and separating the maxilla into halves along the sutura palatina after dissecting the muscles and soft tissues. The maxilla samples were then fixed with 10% formalin (33).…”
Section: Experimental Designmentioning
confidence: 99%
“…In addition to the heart tissues, maxillary samples were taken by decapitating the rats and separating the maxilla into halves along the sutura palatina after dissecting the muscles and soft tissues. The maxilla samples were then fixed with 10% formalin (33).…”
Section: Experimental Designmentioning
confidence: 99%
“…TFPZ inhibited osteoclast formation in mouse bone marrow macrophages (8). CPZ reduced alveolar bone loss in experimental periodontal disease in rats (9). These evidences suggest that phenothiazine derivatives inhibit not only osteoblastic function but also osteoclastic bone resorption.…”
Section: Introductionmentioning
confidence: 67%
“…In previous studies, the anti-bone resorbing effects of phenothiazines were observed in experimental periodontal disease in rats with a nylon thread ligature around the cervix of the second left upper molars in vivo (9) and in calvaria and isolated osteoclast cultures in vitro (5 -7). The bulk of these studies suggesting that the phenothiazine derivatives inhibited bone resorption by inhibiting osteoclast differentiation and the activity were not inconsistent with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for using this experimental period is based on previous investigations. 13,15,23 According to Lima et al, 23 placement of a ligature around the molar teeth of rats leads to the presence of inflammatory cells, including osteoclasts, beneath the ligature. These authors reported that the substantial alveolar bone loss originated on day 3 of periodontitis induction reached a maximum between days 7 and 11.…”
Section: Discussionmentioning
confidence: 99%